Effects of Bamboo Soil and Organic Fertilizer on the Growth and Yield of Dictyophora indusiata Grown in Pots - Saeng-ngoen, Komgrit; Theerak, Winakon (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2026)
This research aimed to evaluate the effects of bamboo soil and organic fertilizer on the growth and yield of Dictyophora indusiata (bamboo mushroom) cultivated in pots. Mushrooms were cultivated in 15-inch pots containing a substrate of bamboo chips, bamboo leaves, and sucrose, amended with five ratios of bamboo soil to organic fertilizer (100:0, 75:25, 50:50, 25:75, and 0:100, w/w). The experiment was arranged in a Randomized Complete Block Design (RCBD) with six replications per treatment. The results showed that the mycelium colonized all substrate ratios within 30 days after inoculation. The substrate with a 0:100 ratio (100% organic fertilizer) induced the fastest fruiting body initiation (pinhead stage) at 38 days after inoculation (p < 0.05). In contrast, the 75:25 w/w ratio resulted in the shortest development period from pinhead to mature stage (14 days) and produced the highest number of fruiting bodies (18.17), but also the highest number of aborted fruiting bodies (12.00) (p < 0.05). Furthermore, the 75:25 w/w ratio yielded fruiting bodies with the greatest fresh weight (58.90 g), stipe length (17.07 cm), stipe diameter (2.73 cm), and veil length (20.10 cm) (p < 0.05). For mushrooms harvested at the egg stage for gel collection, the 100:0 w/w ratio produced the largest egg size (4.78 cm in diameter) (p < 0.05) and the highest gel yield (17.00 g).